Effect of Guar Gum on Processing and Cooking Quality of Nontraditional Pasta. Issue 5 (4th December 2014) - Sandhu, Gurleen K.; Simsek, Senay; Manthey, Frank A.
Abstract The effect on processing and cooking quality of pasta containing nontraditional ingredients and guar gum (GG) was characterized. Durum flour was fortified with soy flour or oat flour and with GG from three different vendors. Physical and chemical properties of GG at three concentrations (0.2, 0.3 and 0.4% w/v) varied among vendors. Protein and lipid contents were highest in soy flour than durum and oat flour. Bulk density, particle size distribution and water‐holding capacity varied among durum flour and all nontraditional ingredients. Mixograms indicated that GG increased dough strength of durum flour and the increased strength varied among vendors. Hydrated ingredients were extruded as spaghetti, and dried using high temperature drying (70C), before pasta quality analysis. The effects of GG and GG vendor on dough strength were manifested in differences in extrusion rate. Guar gum, regardless of vendor, had no effect on the cooking quality of pasta. Practical Applications There has been very limited information on properties, quality characteristics and functionality of the gums from various sources. Also, no literature was found that studied the effect of different commercial sources of guar gum (GG) on the processing properties and cooking quality of pasta containing nontraditional ingredients. Therefore, this study was undertaken with an aim to compare and characterize GG from different vendors of food‐grade gums and their subsequent effects on the processing and cooking quality of pasta containing nontraditional ingredients.